Reliability of using generic flow conditions to quantify aneurysmal haemodynamics: A comparison against simulations incorporating boundary conditions measured in vivo. (October 2022) - Li, Bao; Liu, Tao; Liu, Jincheng; Liu, Youjun; Cao, Boqiang; Zhao, Xi; Wang, Wenxin; Shi, Mengchao; Zhang, Liyuan; Xu, Ke; Chen, Mingyan; Wen, Chuanqi; et al.
Highlights: Aneurysmal haemodynamics of 19 patients were quantified by CFD simulations incorporating physiologically real boundary conditions measured in vivo . Statistically significant difference was found between simulations using generic and patient-specific boundary conditions, in terms of the TAWSS, PIAF, and OSI. Outflow strategies yielded limited variations to the simulated aneurysmal haemodynamics. Steady-state CFD using cycle-averaged boundary conditions achieved WSS and PIAF results similar to those obtained from transient simulations. Abstract: Background and objectives: Initiation, growth, and rupture of intracranial aneurysms are believed to be closely related to their local haemodynamic environment. While haemodynamics can be characterised by use of computational fluid dynamics (CFD), its reliability depends heavily upon accurate assumption of the boundary conditions. Herein, we compared the simulated aneurysmal haemodynamics obtained by use of generic boundary conditions against those obtained under flow conditions measured in vivo . Methods: We prospectively recruited 19 patients with intracranial aneurysms requiring 3-dimensional rotational angiography, during which blood pressure at the internal carotid artery was probed by catheter and flowrate measured by a dedicated software tool. Using these flow conditions measured in vivo, we quantified the aneurysmal haemodynamics for each patient by CFD, and then compared the results with those derived from a generic condition reported in the literature, in terms of the time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI), relative residence time (RRT), and percentage of the intra-aneurysmal flow (PIAF). In addition, the effects on aneurysmal haemodynamics of different outflow strategies (splitting method vs . Murray's Law) and simulation schemes (transient vs . steady-state) relative to each flow condition were also assessed. Results: Differences in the simulated TAWSS (−6.08 ± 10.64 Pa, p  = 0.001), OSI (0.06 ± 0.13, p  = 0.001), and PIAF (−0.05 ± 0.20, p  = 0.012) between the patient-specific and generic boundary conditions were found to be statistically significant, in contrast to that in the RRT (49 ± 307 Pa −1, p  = 0.062). Outflow strategies did not yield statistically significant differences in any of the investigated parameters (all p  > 0.05); rather, the resulting parameters were found to be in good correlations (all r  > 0.71, p  < 0.001). Difference between the aneurysmal TAWSS and the WSS derived from cycle-averaged flowrate condition was found to be minor (0.66 ± 1.36 Pa, p  = 0.000), so was that between PIAFs obtained respectively from the transient and steady-state simulations (0.02 ± 0.05, p  = 0.000). Conclusions: Incorporating into simulation the patient-specific boundary conditions is critical for CFD to characterise aneurysmal haemodynamics, while outflow strategies may not introduce significant uncertainties. Steady-state simulation incorporating the cycle-averaged flow condition may produce unbiased WSS and PIAF compared to the transient analysis. Graphical abstract: Image, graphical abstract